Attitudes and perceived barriers toward healthy lifestyle behaviors in Jordanian adolescents: a developing country perspective - Al-sheyab NA; Alomari MA; Hayajneh AA; Shah S (Dove Medical Press, 2019)
Nihaya A Al-sheyab,1,2 Mahmoud A Alomari,3 Audai A Hayajneh,4 Smita Shah5 1Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid, Jordan; 2Faculty of Nursing, Jordan University of Science and Technology, Irbid, Jordan; 3Division of Physical Therapy, Department of Rehabilitation Sciences, Jordan University of Science and Technology, Irbid, Jordan; 4Adult Health Nursing Department, Faculty of Nursing, Jordan University of Science and Technology, Irbid, Jordan; 5Sydney Medical School, The University of Sydney, Sydney, NSW, Australia Background and aims: There is an urgent need to address the role of healthy diet and behaviors promoting health among school adolescents in order to tailor appropriate interventions in Jordanian schools. This study aims to evaluate the reliability and validity of the Arabic version of Students As LifeStyle Activists (SALSA) survey alongside Jordanian adolescents’ attitudes and perceived barriers to healthy eating and physical activity. Methods: This study uses baseline data from a randomized controlled trial recruiting school students from 29 male and 27 female public high schools that have grades 7 and 8. Cronbach’s alpha and principal components analysis/factor analysis were used to check reliability and validity. Numbers, percentages, and chi square were used to explore healthy diet and physical activities preferences among Jordanian school students and determine gender differences for all evaluated items. Results: The Arabic version-SALSA survey has acceptable Cronbach’s alpha values (>0.78) for most of its scales. Five scales were derived from the Arabic version-SALSA survey using principal components analysis/factor analysis (factors loading above 0.3). A higher proportion of female students agreed that “healthy food makes you more comfortable” compared to male students (44% vs 36%, P<0.05). Few Jordanian high school students held positive attitudes toward healthy food. This study identified both social and personal barriers to exercise among Jordanian adolescents, including lack of skills for physical activity, easy access and low cost of fast food, scarce opportunities for physical activity, and lack of peers and friends. Conclusion: Interventions should be tailored to health attitudes and beliefs of Jordanian school students in parallel with improving physical resources and enhancing peer and/or friend support. Keywords: adolescent, attitude, practices, barriers, lifestyle, peer education, Jordan